Risk and protective factors of neurocognitive disorders in older adults in Central and Eastern Europe: A systematic review of population-based studies - Wolfova, Katrin; Kucera, Matej; Cermakova, Pavla (PloS one, 2021)
BACKGROUND: A wide range of potentially modifiable risk factors, indicating that the onset of neurocognitive disorders can be delayed or prevented, have been identified. The region of Central and Eastern Europe has cultural, political and economic specifics that may influence the occurrence of risk factors and their link to the cognitive health of the population. OBJECTIVE: We aimed to systematically review population-based studies from Central and Eastern Europe to gather evidence on risk and protective factors for neurocognitive disorders. METHODS: We searched the electronic databases PubMed, Cochrane Database of Systematic Reviews, PsycINFO, Web of Science, and Embase. The search was performed on 26th of February 2020 and repeated at the end of the review process on 20th May 2021. RESULTS: We included 25 papers in a narrative synthesis of the evidence describing cardiovascular risk factors (n = 7), social factors (n = 5), oxidative stress (n = 2), vitamins (n = 2), genetic factors (n = 2) and other areas (n = 7). We found that there was a good body of evidence on the association between neurocognitive disorders and the history of cardiovascular disease while there were gaps in research of genetic and social risk factors. CONCLUSION: We conclude that the epidemiological evidence from this region is insufficient and population-based prospectively followed cohorts should be established to allow the development of preventive strategies at national levels.
Keywords: rizikové faktory; Europe, Eastern; východní Evropa; ochranné faktory; Aged; lidé; Protective Factors; senioři; Risk Factors; Humans; Neurocognitive Disorders; neurokognitivní poruchy